Argumentative Text as a Reflection of Non-Language Students' Critical Thinking Skills - Rahayu Fitri; Upit Yulianti DN (PT. Riset Press International, 2026)
This study aims to analyze the critical thinking skills of non-language students in writing argumentative texts. This study uses mixed method with explanatory sequential design. The subjects of this study were non-language students who participated in argumentative text writing lessons. The research data were obtained through argumentative text writing assignments which were then analyzed based on critical thinking ability indicators. The results showed that the critical thinking ability of non-language students in writing argumentative texts was in the high category with an average score of 69,88. In general, students were able to convey claims clearly, provide relevant reasons, and present supporting data or evidence to support their arguments. Students also demonstrated the ability to connect arguments logically and draw conclusions that were in accordance with the discussion. However, some students still experienced difficulties in developing stronger evidence and considering other points of view more deeply. Based on these findings, it can be concluded that argumentative texts can be an effective medium for measuring and developing students' critical thinking skills. Therefore, learning to write argumentative texts needs to be continuously developed with strategies that encourage students to express arguments logically, supported by relevant data, and consider various points of view on a problem. This study contributes to the field of language and literacy education by demonstrating that critical thinking skills can be systematically identified through the analysis of argumentative texts produced by students from non-language disciplines. Unlike previous studies that predominantly focus on language learners, this research provides empirical insights into how argumentative writing reflects critical thinking processes among non-language students, thereby expanding the scope of critical thinking assessment in higher education.